Disseram que voltei americanizada : a construção da imagem de Carmen Miranda pelos meios de comunicação - Raslan, Eliane Meire Soares (2014)
We analysed in this thesis the construction of the image of the actress and singer Carmen Miranda, especially by the film industry, and how the artist influenced the attitudes and habits of some populations, mainly the Brazilian and American people. The method of discourse analysis was used to evaluate the image of Carmen Miranda in the various existing media, highlighting its connection to Hollywood cinema, between 40 and 50, especially with regard to the construction of cultural identity. In order to complement the Discourse Analysis, we utilized the Depth Hermeneutics, with the aim to understand how different symbols were produced from the same image in different populations. We also checked the symbolic language and the representation of the figure of the actress to support the idea of audiovisual handling of latin and american viewers by cinema. The cinema had its cathartic role: the U.S. population wanted to watch "Bombshell" to forget about the war, whereas the Brazilian people felt accepted - recognized - before the figure of Carmen Miranda in foreign cinema. The Hollywood movies in which Carmen Miranda participated had great worldwide impact, marking the peak of her career. They pleased, a lot the U.S. mass. On the other hand, the Latin people did not like the way Carmen was shown in the movies, because they felt offended and poorly represented. This offense was overcome by changes in the script and the great international success of the actress, who kept the Bahia clothing, estabilishing her identity. Beyond Hollywood overproduction, the cinema has always aroused interest in Latin American society, who used to make the movies theater packed. Lay behind these films other Latino looks like "charm" of the big screen movie and disclosure of grand spectacles of Hollywood films which had not existed as a form of entertainment (film vehicle communication) in their societies. In Brazil, which had its fledgling movie theaters and movie productions sponsored and controlled by the United States, these effects were even greater.